The role of aryl hydrocarbon receptor (AhR) in carcinogenesis in people with high level of dioxin - Dung, Lê Thị Kim; Liên, Nguyễn Thị Kim; Hoàng, Nguyễn Huy; Hải, Nông Văn (Vietnam Journal of Biotechnology, 2018)
The Aryl hydrocarbon receptor (AhR) is a ligand activated transcription factor that is best known for mediating the toxicity and tumor promoting properties of the carcinogen, including of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD - dioxin). Numerous studies for harmful effects on human health of dioxin have been studied. The results showed that dioxin had effects on many of tissues and organs of nerve system, immune system, reproductive system leading to birth defects and causing development of cancers. The AhR is also now known to be involved in a variety of cellular processes, such as the cell cycle, epithelial barrier function, cell migration,and immune function. Through the AhR, dioxin influences the major stages of tumorigenesis- initiation, promotion, progression, and metastasis. Studies of aggressive tumors and tumor cell lines have revealed that AhR levels are elevated and can be found constitutively in the nucleus. A high degree of complexity has emerged regarding the role of AhR in cancer, with clear discrepancies between pro- and anti-tumorigenic activities when utilizing cell culture versus in vivo models of malignancy. Furthermore, various classes of AhR ligands and indeed ligands within the same class can differentially modulate AhR to influence tumorigenic outcomes. This leads to the hypothesis that the AhR is chronically activated in tumors, thus facilitating tumor progression. In this article, we review the results of studies in the literature about the role of AhR in carcinogenesis in humans with high level of dioxin. Information of the influence of AhR on the formation and development of tumors will be useful understanding to develop potential therapeutic modulation through AhR activities in tumors and to provide effective treatment for cancer patients.